2015
DOI: 10.1007/s10571-015-0159-9
|View full text |Cite
|
Sign up to set email alerts
|

Wharton’s Jelly Transplantation Improves Neurologic Function in a Rat Model of Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI), which can lead to disability, dysfunction, and even death, is a prominent health problem worldwide. Effective therapy for this serious and debilitating condition is needed. Human umbilical cord matrix, known as Wharton's jelly (WJ), provides a natural, interface scaffold that is enriched in mesenchymal stem cells. In this study, we tested the efficacy of WJ tissue transplantation in a weight drop model of TBI in rats. WJ tissue was cultured and transplanted into the injury site 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…Brain water content was measured on day 3 after TBI, as described previously [41]. Mice were euthanized by decapitation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain water content was measured on day 3 after TBI, as described previously [41]. Mice were euthanized by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…A 3-mm coronal section around the major area of injury was collected in ice-cold PBS with a mouse brain slicer matrix (Zivic Instruments, Pittsburgh, PA) [15, 41]. We used the Nuclear Extraction Kit (Origene, Rockville, MD) to isolate cytosolic and nuclear protein fractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-eight studies met inclusion criteria and underwent data extraction and quality assessment. Of these studies, some reported more than one pertinent outcome measure so that a total of 10 studies presented data for RR outcomes (1625), 14 presented data on LV outcomes (23, 2638), 21 assessed NSS outcomes (1721, 2326, 28, 29, 31, 36, 3853), and 13 presented data on MWM testing (17, 18, 24, 26, 28, 29, 36, 38, 4953). Specific study characteristics are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Another important trait of these cells is their immunomodulatory properties. They can suppress immune response through inhibition of T cells, B cells, NK cells and dendritic cells [12][13][14].…”
Section: Introductionmentioning
confidence: 99%